Lipomodelling - advanced technique for the correction of Congenital hypoplastic breast malformations and deformities - Streit, L; Dražan, L; Novák, P; Schneiderová, M; Dvořák, Z; Teplá, K; Veselý, J (Acta chirurgiae plasticae, 2016)
A variety of surgical techniques has been used to correct hypoplastic breast malformations and deformities, including tissue expanders, breast implants, custom chest wall implants, mammary gland remodelling, as well as locoregional or free flap. Case series of successful breast reconstruction using lipomodelling technique in one patient with severe Polands syndrome and two patients with tuberous breasts are reported together with literature review. No surgical complications were observed and ultrasound examination did not reveal any pathology in breast tissue other than oil pseudocysts postoperatively. In both malformations, submammary fold was moved downwards. Moreover, the lower part of the breast and areolar herniation was corrected in tuberous breast, and in Polands syndrome, the areolar complex was significantly shifted downwards and laterally. In comparison with other reconstructive techniques, lipomodelling allows for the breast correction to begin in early adolescence. Further growth of the unaffected breast may be effectively corrected by subsequent lipomodelling session. This technique appears to change the overall approach to the management of hypoplastic breast and chest wall malformations.
Keywords: Humans; breast; fat grafting lipomodelling.; mladý dospělý; prsy; Polandův syndrom; tuková tkáň; Adipose Tissue; tuberous; malformation; Congenital; Adolescent; Breast; Poland Syndrome; ženské pohlaví; Mammaplasty; lidé; mladiství; constricted; Polands syndrome; Young Adult; mamoplastika; Female